Islamic economics, banking, and finance literature bibliometrics approach: Guideline for journal databases - Indri Supriani; Ujang Syahrul Mubarrok (Review of Islamic Social Finance and Entrepreneurship, 2023)
Purpose – This paper aims to present a comprehensive understanding of performing a bibliometric study that uses a journal as the research data. Moreover, this study also aims to offer guidelines for conducting bibliometric analysis that provides a meaningful discussion about the journal's performance, particularly in Islamic Economics, Banking, and Finance (IEBF) field.Methodology – This study discussed bibliometric as a methodology by adopting a literature review approach on four selected bibliometric articles in the IEBF field that use a journal as their research data. Previous bibliometric studies on IEBF that utilize journals as their research data have a commonality in selecting the journal based on the adequacy and availability of data and the journal's position and impact.Findings – This study highlighted the most used metrics and techniques to present the journal's performance. Importantly, this study suggested that future research must elaborate their findings with the current facts and academic reasons to enrich the discussion.Implications – This study will be benefited the journal editors and scholars in adopting appropriate bibliometric analysis that uses a particular journal as the research data. Consequently, this study will contribute to enhancing the research quality of IEBF.Originality – This study is a pioneer attempt to propose a bibliometric research guideline that utilizes specific journals as the research data.